Effect of smoking status on the efficacy of the SMART regimen in high risk asthma - Pilcher, Janine; Patel, Mitesh; Reddel, Helen K.; Pritchard, Alison; Black, Peter; Shaw, Dominick E.; Holt, Shaun; Weatherall, Mark; Beasley, Richard (Wiley, 2016)
Background and objective: The optimal management of people with asthma with a significant smoking history is uncertain. The aim of this study was to determine whether the efficacy/safety profile of single combination inhaled corticosteroid (ICS)/long acting beta-agonist (LABA) inhaler maintenance and reliever therapy is influenced by smoking status. Methods: We undertook secondary analyses from an open-label 24-week randomized study of 303 high risk adult asthma patients randomized to budesonide/formoterol 200/6-µg-metred dose inhaler for maintenance (two actuations twice daily) and either budesonide/formoterol 200/6-µg-metred dose inhaler one actuation (‘single ICS/LABA maintenance and reliever therapy (SMART)’ regimen) or salbutamol 100 µg 1–2 actuations for symptom relief (‘Standard’ regimen). Smoking status was classified in to three groups, as ‘current’, ‘ex’ or ‘never’, and a smoking/treatment interaction term tested for each outcome variable. The primary outcome variable was number of participants with at least one severe exacerbation. Results: There were 59 current, 97 ex and 147 never smokers included in the analyses. The smoking status/treatment interaction term was not statistically significant for any of the outcome measures. With adjustment for smoking status, the number of participants with severe exacerbations was lower with the SMART regimen (OR 0.45, 95% CI: 0.26–0.77, P = 0.004; P value for interaction between smoking status and treatment 0.29). Conclusion: We conclude that the favourable safety/efficacy profile of the SMART regimen applies to patients with high risk asthma, irrespective of smoking status.